Serum profiling of uPA, PAI-1, and suPAR in systemic sclerosis: a preliminary study on analytical aspects and associations with microvascular and fibrotic manifestations - Napolitano, Filomena; Mormile, Ilaria; Mignogna, Gabriele; de Paulis, Amato; Rossi, Francesca Wanda; Montuori, Nunzia (Frontiers in Immunology, 2025)
IntroductionIn systemic sclerosis (SSc), the laboratory panel lacks biomarkers able to predict the disease course and/or reflect the fibrotic activity in the skin and internal organs. We assessed the association of the serum levels of urokinase (urokinase plasminogen activator, uPA), plasminogen activator inhibitor-1 (PAI-1), and soluble urokinase plasminogen activator receptor (suPAR) with the microvascular and fibrotic manifestations.MethodsA total of 21 patients with SSc were enrolled in the study. The serum levels of PAI-1, uPA, and suPAR were measured using ELISA, and the diagnostic performance of two widely debated suPAR ELISA kits, i.e., Human suPAR ELISA (Biovendor R&D, Brno, Czech Republic) and suPARnostic ELISA (Virogates, Copenaghen, Denmark), was examined in patients with SSc and in healthy controls. The serum uPA, PAI-1, and suPAR levels were correlated with the typical fibrotic and vascular markers, such as TGF-β1 and VEGF-A, the anti-Scl-70 antibodies, and the nailfold capillaroscopic abnormalities and pulmonary function indicators.ResultsLower circulating uPA (3,226 ± 2,444 pg/ml) and higher PAI-1 (95.30 ± 22.80 ng/ml) and suPAR (2.522 ± 1.186 ng/ml with Human suPAR ELISA and 3.835 ± 2.944 ng/ml with suPARnostic ELISA) levels were found in patients with SSc. Both suPAR assays showed high sensitivity and specificity for SSc. However, suPAR measured using the suPARnostic assay displayed stronger associations with the clinical manifestations, indicating its potential as a marker of disease severity. uPA was negatively correlated with TGF-β1 (p=0.008), whereas PAI-1 and suPAR (measured with the suPARnostic assay) were positively correlated with VEGF-A (p=0.01 and p=0.03, respectively). Furthermore, higher suPAR levels obtained with the suPARnostic assay, but not with Human suPAR ELISA, were associated with microvascular and fibrotic manifestations.ConclusionThis preliminary study provides meaningful evidence supporting the potential of suPAR as a marker of disease severity in SSc and the impact of method-related differences in the levels of suPAR.